2011
DOI: 10.1186/1471-2458-11-538
|View full text |Cite
|
Sign up to set email alerts
|

Non prescribed sale of antibiotics in Riyadh, Saudi Arabia: A Cross Sectional Study

Abstract: BackgroundAntibiotics sales without medical prescriptions are increasingly recognized as sources of antimicrobial misuse that can exacerbate the global burden of antibiotic resistance. We aimed to determine the percentage of pharmacies who sell antibiotics without medical prescriptions, examining the potential associated risks of such practice in Riyadh, Saudi Arabia, by simulation of different clinical scenarios.MethodsA cross sectional study of a quasi-random sample of pharmacies stratified by the five regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
207
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(244 citation statements)
references
References 30 publications
16
207
2
3
Order By: Relevance
“…[5][6][7][8] A simulated patient demanded medication for pain located in the region of the frontal sinuses. The other information regarding the simulated patient was listed as following; he was purchasing this medication for his wife, who was 24 years old; she had a fever of 38-38.5 o C, she also had running nose; she had a history of rhinosinusitis and she had used antibiotics in the past, but she could not remember the name of the antibiotic; she was currently only using oral contraception and had no history of allergies.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] A simulated patient demanded medication for pain located in the region of the frontal sinuses. The other information regarding the simulated patient was listed as following; he was purchasing this medication for his wife, who was 24 years old; she had a fever of 38-38.5 o C, she also had running nose; she had a history of rhinosinusitis and she had used antibiotics in the past, but she could not remember the name of the antibiotic; she was currently only using oral contraception and had no history of allergies.…”
Section: Data Collectionmentioning
confidence: 99%
“…5 However, in many simulated patient studies, it has been observed that antibiotics which were suggested without prescription were common in cases with acute uncomplicated rhinosinusitis or other acute infections. [5][6][7][8] According to the report by the Turkish Ministry of Health based on records of Prescription Information System in 2011 and 2012, it was determined that the rate of prescribing antibiotics by general practitioners were approximately 35.0% and 34.0%, respectively. 9 The elevated utilization of antibiotics is not unique to Turkey and other developing countries; it is also common in Europe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be compounded by irrational practices of prescribing antibiotics mainly for upper respiratory infections [13][14][15][16], and immature antibiotics stewardship policies. This may be complicated by the availability of antibiotics without prescription (regulated but not controlled) [17][18][19] and lack of laboratories for antibiotics susceptibility testing and surveillance. Factors such as; lack of access to health care services, services are not affordable, limited regulatory control of the use of prescription medicines including antibiotics, limited understanding of the role of antibiotics, the opportunity to self-medicate, the concern of doctors for the risk of secondary bacterial infections after viral illnesses in poor environments, prohibitive cost sensitivity testing and pharmaceutical promotional tactics all compound the problem [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one can easily buy prescription-only medicines, such as antibiotics, without a prescription despite the strict regulations [12].…”
Section: Introductionmentioning
confidence: 99%